1999
DOI: 10.2337/diacare.22.5.713
|View full text |Cite
|
Sign up to set email alerts
|

An office-based intervention to maintain parent-adolescent teamwork in diabetes management. Impact on parent involvement, family conflict, and subsequent glycemic control.

Abstract: The data demonstrate that parent involvement in diabetes management tasks can be strengthened through a low-intensity intervention integrated into routine follow-up diabetes care. Moreover, despite increased engagement between teen and parent centered around diabetes tasks, the teamwork families showed decreased diabetes-related family conflict. Within the context of a broader cultural recognition of the protective function of parent involvement in the lives of adolescents, the findings of this study reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
301
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(313 citation statements)
references
References 0 publications
10
301
1
1
Order By: Relevance
“…As some research indicated (e.g. Anderson, Brackett, Ho, & Laffel, 1999;Conger & Donnellan, 2007), families' illness-related interactions significantly influence patient outcomes. Despite these limitations, our findings raise a number of new questions.…”
Section: Discussionmentioning
confidence: 99%
“…As some research indicated (e.g. Anderson, Brackett, Ho, & Laffel, 1999;Conger & Donnellan, 2007), families' illness-related interactions significantly influence patient outcomes. Despite these limitations, our findings raise a number of new questions.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study of adolescents demonstrated that targeted improvements in conflict resolution and sharing of diabetes management responsibilities were maintained over 1 year (B. J. Anderson et al, 1999).…”
Section: The Need For User-friendly Easily Accessible and Cost-effementioning
confidence: 99%
“…Intervention that emphasizes the importance of adolescents and parents sharing responsibility for diabetes management appears to enhance continued parental involvement (B. J. Anderson, Brackett, Ho, & Laffel, 1999). Because habits in diabetes care established early tend to persist over time (Jacobson et al, 1990), several researchers have suggested that programs need to be implemented soon after diagnosis (B. J.…”
Section: Family Interventionsmentioning
confidence: 99%
“…The next most critical goal is the adaptation of established parenting education curricula, such as the Systematic Training for Effecting Parenting (STEP) program 23 and Raising an Emotionally Intelligent Child, 24 which are based on the concepts of parenting styles discussed earlier and into which could be integrated proven pediatric behavioral diabetes family-based interventions, such as Coping Skills Training, 25 Behavioral Family Systems Therapy, 26 and Family Teamwork. 27 For diabetes health care providers, the child development literature instructs us to help parents build, if necessary, a new parenting style specific to diabetes management.…”
Section: From Research To Practice / Children and Families Living Witmentioning
confidence: 99%